Encounters with Modernism : Highlights from the Stedelijk Museum Amsterdam - Bertheux, Maarten; Groenink, Rijkman; Kwok Kian Chow; Li Xiang Yang; Suenne Megan Tan; van Beers, Hans (Amsterdam : Stedelijk Museum Amsterdam, 2004)
Andre, Carl ; Appel, Karel ; Baselitz, Georg ; Constant ; Copley, William ; Cragg, Tony (Anthony) ; Daniels, René ; Dibbets, Jan ; Dijkstra, Rineke ; Domela, César ; Dubuffet, Jean ; Duchamp, Marcel ; Dumas, Marlene ; van Elk, Ger ; Fontana, Lucio ; Förg, Gunther ; Gilbert & George ; Gordon, Douglas ; Gursky, Andreas ; Guston, Philip ; Halley, Peter ; Haring, Keith ; Herold, Georg ; Jorn, Asger ; Judd, Donald ; Kaap, Gerald Van Der ; Kandinsky, Wassily ; Kappl, Franco ; Kirchner, Ernst Ludwig ; de Kooning, Willem ; Koons, Jeff ; Kounellis, Jannis ; LeWitt, Sol ; Longo, Robert ; Mangold, Robert ; Martin, Agnes ; Merz, Mario ; Mik, Aernout ; Mondriaan, Piet ; Mulders, Marc ; Nauman, Bruce ; Newman, Barnett ; Oldenburg, Claes ; Paik, Nam June ; Picasso, Pablo ; Pollock, Jackson ; Post, Liza May ; Preesman, Avery ; Raedecker, Michael ; Rainer, Arnulf ; Rosenquist, James ; Rothko, Mark ; Ryman, Robert ; Salle, David ; Saul, Peter ; Saura, Antonio ; Scharf, Kenny ; Schmidt-Rottluff, Karl ; Schnabel, Julian ; Schouten, Marien ; Schuil, Han ; Severini, Gino ; Sherman, Cindy ; Stella, Frank ; Tàpies, Antoni ; Warhol, Andy ; Wiegers, Jan ; Zandvliet, Robert
Encounters with Modernism : Highlights from the Stedelijk Museum Amsterdam, Museu de Arte Moderna, Rio de Janeiro, Pinacoteca do Estado São Paulo. SAM (Singapore Art Museum) Singapore. Shanghai Art Museum Shanghai, Stedelijk Museum Amsterdam, 2004-01-14. 2004-03-18, 2004-07-18. 2004-10-20, 2004-02-20. 2004-06-06, 2004-10-03. 2005-01-09
boek
Keywords: Rio de Janeiro; Sao Paulo; Shanghai; Singapore